For the categorisation of historic buildings to determine energy saving - Tor Broström; Anna Donarelli; Fredrik Berg (Agathón)
Technical characteristics and cultural values affect the possibility of saving energy in the historic building stock. The issue has been addressed and studied in monumental buildings. For the majority of historic buildings, defined in this research as traditional constructions built before 1945 when the building sector became more industrialised, there is still a need for further studies. The aim of this article is to present the development of a method to categorise a historic building stock with the ability to identify the potential for energy saving and preservation of cultural values. This study has been conducted within the multi-disciplinary projects Potential and policies for energy efficiency in Swedish buildings built before 1945, financed by the Swedish Energy Agency and Energy Efficiency for EU Historic Districts, funded by the European Commission under its Seventh Framework Programme.